Economics : 6th edition - Begg David; Fischer Stanley; Dornbusch, Rudiger (London : McGraw Hills, 2000)
It provides a definitive introduction to economics in the twenty-firt century. The text includes a new chapter on the information Economy, with additional material on economic issues facing Europe and the rest of the world.
Incudes index (Includes updated student CD-ROM)
uaj 25/02/2015
Loans
Keywords: Economics